Optimized pacing strategies in cross-country skiing and time-trial road cycling - Sundström, D. (2013)
This thesis is devoted to the analysis and optimization of pacing strategies in cross-country skiing and time-trial road cycling. In locomotive sports, it is well known that variable pacing strategies using changes in the distribution of power output are beneficial when external forces vary along the way. However, there is a lack of research that more in detail investigates the magnitude of power output alteration necessary to optimize performance.A numerical program has been developed in the MATLAB software to simulate cross-country skiing and time-trial road cycling, as well as pacing strategy optimization in these two locomotive sports. The simulations in this thesis are performed by solving equations of motion, where all the main forces acting on the athlete are considered. The motion equations also depend on the course profile, which is expressed as a connected chain of cubical splines.The simulation process is linked to an optimization routine called the Method of Moving Asymptotes (MMA), which strives to minimize the finishing time while altering the power output along the course. To mimic the human energetic system, the optimization is restricted by behavioural and side constraints.Simple constraints like maximum average power output are used for cross-country skiing in Papers I and II. In Paper III a more sophisticated and realistic constraint is used for the power output in time-trial road cycling. It is named the concept of critical power for intermittent exercise and combines the aerobic and anaerobic contributions to power output.In conclusion, this thesis has demonstrated the feasibility of using numerical simulation and optimization in order to optimize pacing strategies in two locomotive sports. The results are clearly showing that these optimized pacing strategies are more beneficial to performance than an even distribution of power output